Mainstreaming in the right of accessibility: reasonable accommodation in the local field as in the political and social participation - Rojas Buendía, María del Mar (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
Some considerations on the rights of persons with functional diversity, have to see today with elements such as accessibility and the reasonable adjustments in the «urban local space», and invite a philosophical reflection, political-legal and socio-economic together, which relates to the right to have rights and with its speech. doi: https://doi.org/10.20318/universitas.2017.3560